Physical and chemical properties of multifunctional ZnO nanostructures prepared by precipitation and hydrothermal methods - Sumetha Suwanboon (2018)
Spherical, cabbage-like and flower-like ZnO powders were prepared by precipitation and hydrothermal methods. Zn(CH3COO)2·2H2O, KOH, distilled H2O and C3H9N were used as the zinc source, precipitating agent, solvent and capping agent, respectively. The ZnO powders were characterized by TGA, FTIR, XRD and SEM. The particle shape of the ZnO powders altered when the solution was modified by n-propylamine. The photocatalytic activity of the ZnO powders depended on the particle shape whilst the bactericidal property of the ZnO powders was influenced by both particle shape and defect concentration. © 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.